1989
DOI: 10.1017/s002193200001782x
|View full text |Cite
|
Sign up to set email alerts
|

Polygamy and fertility in Somalia

Abstract: SummaryThe 1983 Somali Family Health Survey showed that polygamy and monogamy selected women with different social characteristics. Wives in polygamous unions were prone to be younger at first marital cohabitation and to have previous marital disruptions. Since a young age at first cohabitation and number of previous marriages have opposite effects on the cumulative fertility rate of women, the difference in this rate between wives in polygamous and monogamous unions vanished when both factors were controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
1
6
1
Order By: Relevance
“…The proportion of wives who married when they were under 15 years old was lower among junior and monogamous wives. This finding is consistent with previous reports showing that wives in polygamous unions were prone to be younger at first marital cohabitation (Johnson & Elmi, 1989, Al-Krenawi et al, 1997. Shane (1990) reported that the average age at marriage in Turkey has risen from 17.6 years to 18.2 years between 1983 and 1988; the proportion of single women under 25 years of age increased by 17% in the same period.…”
Section: Discussionsupporting
confidence: 93%
“…The proportion of wives who married when they were under 15 years old was lower among junior and monogamous wives. This finding is consistent with previous reports showing that wives in polygamous unions were prone to be younger at first marital cohabitation (Johnson & Elmi, 1989, Al-Krenawi et al, 1997. Shane (1990) reported that the average age at marriage in Turkey has risen from 17.6 years to 18.2 years between 1983 and 1988; the proportion of single women under 25 years of age increased by 17% in the same period.…”
Section: Discussionsupporting
confidence: 93%
“…This is also contrary to other findings where boy preference exerts a significant effect on fertility (18,19). Other studies indicated insignificant influence of sex preference on fertility (16,(20)(21)(22).…”
Section: Discussioncontrasting
confidence: 78%
“…In line with evolutionary theory, polygamy is said to be beneficial to male reproductive success as it leads to larger numbers of surviving offspring [6]. Studies have shown that women in polygamous marriages (the form of marriage prevalent in the area where this study was conducted) are less likely to use contraception [7,8], and competition for more and more children among co‐wives may be a major factor in their avoiding contraception. Moreover, in polygamy, women depend more on their children in later years than do men, who can receive support from younger wives, and may therefore want to have many children.…”
Section: Introductionmentioning
confidence: 75%
“…The effect of polygamy on fertility and therefore on contraception use has puzzled demographers, who are still divided on the issue. Some studies have concluded that polygamy has no effect on contraception use and therefore on fertility [19,23], whereas others have concluded that polygamy is associated with nonutilization of contraceptives [7,8]. It was suggested that changes in reproductive behavior are taking place in Nigeria, and that these changes are restricting fertility in polygamous marriages [21].…”
Section: Discussionmentioning
confidence: 99%